2012
DOI: 10.1038/sc.2012.85
|View full text |Cite
|
Sign up to set email alerts
|

Time of physical exercise practice after injury in cervical spinal cord-injured men is related to the increase in insulin sensitivity

Abstract: Objectives: Physical exercise has an important role in reducing body fat, risk of chronic disease and systemic inflammation. The aim of this study was to determine serum leptin and insulin concentrations and their relationship to the time of physical exercise after injury in men with cervical spinal cord injury (c-SCI). Methods: c-SCI subjects with lesion level in C5-C7 (n ¼ 25) were divided into two groups: physically active (PA, n ¼ 13; those who practiced physical exercise for at least 3 months, three times… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 22 publications
(41 reference statements)
1
8
0
1
Order By: Relevance
“…Similar results despite the differences in subject populations were also cited by Hicks and Ginis (2008) (22) who found that BWSTT (2 -3 sessions/week) decreases total body fat. Recently, in accordance with our research Koury et al (23), illustrated that despite of difference in age, type of training, exercise duration and spinal cord injury level ,three months physical training decreased total body mass (-13%), body mass index (-16%), and fat mass (-39%). Our study is inconsistent with some research reported that LT had no effect on body fat percent in iSCI (24,25).…”
Section: Discussionsupporting
confidence: 67%
“…Similar results despite the differences in subject populations were also cited by Hicks and Ginis (2008) (22) who found that BWSTT (2 -3 sessions/week) decreases total body fat. Recently, in accordance with our research Koury et al (23), illustrated that despite of difference in age, type of training, exercise duration and spinal cord injury level ,three months physical training decreased total body mass (-13%), body mass index (-16%), and fat mass (-39%). Our study is inconsistent with some research reported that LT had no effect on body fat percent in iSCI (24,25).…”
Section: Discussionsupporting
confidence: 67%
“…70 Being physically active has further been linked to a reduction in total body mass, fat mass, C-reactive protein, insulin, and leptin, and more favourable profiles are associated with individuals who begin regular activity closer to the point of their injury. 71 The relationship between aerobic exercise and indices of cardiovascular health are not as well established, although VO 2peak has been shown to be predictive of insulin sensitivity, 72 and exercise training protocols using either ACE or WCE have been shown to improve high density lipoprotein-cholesterol concentrations and reduce the total cholesterol/high density lipoprotein-cholesterol (TC/HDL-C) ratio. 73,74…”
Section: Exercise Interventions To Improve Health and Disease Riskmentioning
confidence: 99%
“…O uso do DEXA para análise da CC em pessoas com lesão medular é, sem dúvida, o mais comumente utilizado nos estudos encontrados, principalmente no exterior (JONES; LEGGE; GOULDING, 2003;SPUNGEN et al, 2003;MODLESKY et al, 2004;GATER, 2005;MANNS;MCCUBBIN;WILLIAMNS;KAYA et al, 2006;YILMAZ et al, 2007;EDWARDS et al, 2008;FORREST et al, 2008;MARUYAMA et al, 2008;GRIFFIN et al, 2009;MORSE et al, 2009;GORGEY et al, 2010a;HALSTEAD et al, 2010;CRANE et al, 2011;RIBEIRO et al, 2011;DOLBOW et al, 2012;AÑÓ et al, 2012;KOURY et al, 2013). O uso frequente do DEXA neste tipo de análise justifica-se por ter se mostrado um instrumento eficiente capaz de identificar indivíduos com percentagens de gordura corporal consistentes com a obesidade, quando parâmetros como medições de prega cutânea e análise por bioimpedância, e indiretos, como o IMC, classificam o indivíduo com estado nutricional normal (limítrofe) (CRANE et al, 2011).…”
Section: Dexa -Dual Energy X-ray Absorptiometryunclassified